Ectomesenchymal chondromyxoid tumour: an uncommon characteristic tumour of the anterior tongue. Issue 10 (25th October 2019) - Riju, Jeyashanth; Ahamed, Shameer; Thomas, Regi; Telugu, Ramesh Babu
Abstract : Ectomesenchymal chondromyxoid tumour (ECMT) is a rare benign tumour which classically presents in the anterior tongue. This tumour is grossly under-reported due to lack of immunohistochemical staining in many centres. We report a 46-year-old man who presented with mass in the anterior tongue and was diagnosed with ECMT. Further management of this lesion is explained with a review of the literature.